2022
DOI: 10.1101/2022.06.24.497443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition to self-compatibility associated with dominantS-allele in a diploid Siberian progenitor of allotetraploidArabidopsis kamchaticarevealed byArabidopsis lyratagenomes

Abstract: A transition to selfing can be beneficial when mating partners are scarce, for example, due to ploidy changes or at species range edges. Here we explain how self-compatibility evolved in diploid SiberianArabidopsis lyrata, and how it contributed to the establishment of allotetraploidA. kamchatica. First, we provide chromosome-level genome assemblies for two self-fertilizing diploidA. lyrataaccessions, one from North America and one from Siberia, including a fully assembled S-locus for the latter. We then propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 151 publications
(130 reference statements)
1
9
0
Order By: Relevance
“…We therefore assembled the genomes of two accessions from the sister species A. lyrata. The two accessions, North American MN47 and Siberian NT1, represent sub-specific A. lyrata lineages that diverged at least ~90,000 years ago [23][24][25][26] . The A. lyrata centromere satellite array assemblies were gapless, and sequence comparisons of syntenic centromeres with A. thaliana indicated that these regions were significantly different between the two species (Fig.…”
Section: Rapid Interspecies Centromere Evolution Between a Thaliana A...mentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore assembled the genomes of two accessions from the sister species A. lyrata. The two accessions, North American MN47 and Siberian NT1, represent sub-specific A. lyrata lineages that diverged at least ~90,000 years ago [23][24][25][26] . The A. lyrata centromere satellite array assemblies were gapless, and sequence comparisons of syntenic centromeres with A. thaliana indicated that these regions were significantly different between the two species (Fig.…”
Section: Rapid Interspecies Centromere Evolution Between a Thaliana A...mentioning
confidence: 99%
“…Arabidopsis lyrata was grown in the greenhouse at 21 o C under 16 hours of light 26 . HMW DNA was isolated from 1.5 g of plant material using a NucleoBond HMW DNA kit 26 .…”
Section: Genomic Dna Extraction and Pacbio Hifi Sequencing From A Lyratamentioning
confidence: 99%
“…This genome has served as reference for functional, ecological, and evolutionary experiments in A. lyrata and also A. arenosa (Arnold et al., 2016; Bjerkan et al., 2020; Klosinska et al., 2016; Lafon‐Placette et al., 2017; Yant et al., 2013). A. lyrata has also been used as the reference for Arabidopsis reference‐guided assemblies (Burns et al., 2021; Jaegle et al., 2023; Kolesnikova et al., 2023; Paape et al., 2018). The genus Arabidopsis has been extensively sequenced, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the GSI system of Solanaceae, self‐polyploidization leads to self‐compatibility (SC; Takayama & Isogai, 2005; Robertson et al ., 2011; Zenil‐Ferguson et al ., 2019). In Brassicaceae, autopolyploids typically maintains the SI system of the ancestral species (Dart et al ., 2004; Hollister et al ., 2012; Hohmann et al ., 2014; Novikova et al ., 2016), while allopolyploids often transition to SC (Okamoto et al ., 2007; Tsuchimatsu et al ., 2012; Novikova et al ., 2017; Bachmann et al ., 2021; Kolesnikova et al ., 2022). In Brassica , all the diploid species belonging to U's triangle ( B. rapa , B. oleracea and B. nigra ) exhibit self‐incompatibility, whereas the allotetraploids ( B. napus , B. juncea and B. carinata ) derived from them are self‐compatible (Nagaharu, 1935).…”
Section: Discussionmentioning
confidence: 99%
“…The above results suggest that the dominant non‐functional S ‐haplotype inhibiting the SI function of the recessive S ‐haplotype is a common occurrence in B. napus . Furthermore, similar mechnisms of self‐compatibility have been observed in allopolyploids of other Brassicaceae genera, such as Arabidopsis suecica , Arabidopsis kamchatica , and Capsella bursa‐pastoris (Novikova et al ., 2017; Bachmann et al ., 2021; Kolesnikova et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%